2012
DOI: 10.5194/amt-5-2309-2012
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas measurements over a 144 km open path in the Canary Islands

Abstract: Abstract.A new technique for the satellite remote sensing of greenhouse gases in the atmosphere via the absorption of short-wave infrared laser signals transmitted between counter-rotating satellites in low Earth orbit has recently been proposed; this would enable the acquisition of a longterm, stable, global set of altitude-resolved concentration measurements. We present the first ground-based experimental demonstration of this new infrared-laser occultation method, in which the atmospheric absorption of CO 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The first proof-of-concept experiment, which is described by Brooke et al (2012) (referred to as Betal2012 hereafter) and gives a technical overview of the ground-based experiment with preliminary results on CO 2 , was performed between La Palma and Tenerife in the Canary Islands in July 2011 (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The first proof-of-concept experiment, which is described by Brooke et al (2012) (referred to as Betal2012 hereafter) and gives a technical overview of the ground-based experiment with preliminary results on CO 2 , was performed between La Palma and Tenerife in the Canary Islands in July 2011 (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…wind speed (from LIO), jointly forming the LEO-LEO microwave and infrared laser occultation (LMIO) method .The retrieval of thermodynamic variables and greenhouse gases is well understood from a range of studies employing end-to-end simulations of the LMIO method. After the introduction of LMIO by Kirchengast and Schweitzer [2011] (linking for further details to the scientific reports by Kirchengast et al [2010] and Schweitzer [2010]), an up-to-date assessment of the LMO retrieval performance for thermodynamic profiles was provided by Schweitzer et al [2011a], a full LMIO clear-air retrieval performance assessment with focus on greenhouse gases was provided by Proschek et al [2011], an analysis of LIO signal propagation and signal-to-noise ratio aspects was provided by Schweitzer et al [2011b], and a study on LMIO greenhouse gas retrieval performance in cloudy air, accounting for scintillations from turbulence, was provided by Proschek et al [2014].An initial LIO ground demonstration experiment for greenhouse gas measurements over a 144 km cross-link at the Canary Islands was conducted as well [Brooke et al, 2012;Proschek et al, 2015] and needs for improved spectroscopic knowledge of target absorption lines for LIO laser signals were investigated [Harrison et al, 2011;Proschek et al, 2015].…”
mentioning
confidence: 99%
“…An initial LIO ground demonstration experiment for greenhouse gas measurements over a 144 km cross-link at the Canary Islands was conducted as well [Brooke et al, 2012;Proschek et al, 2015] and needs for improved spectroscopic knowledge of target absorption lines for LIO laser signals were investigated [Harrison et al, 2011;Proschek et al, 2015].…”
mentioning
confidence: 99%
“…Xia et al (2008) demonstrated diode laser-based CH 4 detection at a minimum detection limit of 1.1 ppm m 21 with a 120-m optical pathlength but did not address in situ instrument drift. Brooke et al (2012) demonstrated 144-km openpath CO 2 measurements with ;4% accuracy across two mountaintops with a low-power diode laser-based occultation technique. Although they claimed the technique is easily extended to CH 4 measurements, the sensor was not calibrated in situ and long-term stability of the retrievals was not quantified.…”
Section: Introductionmentioning
confidence: 99%